Assessing Reservoir Largemouth Bass Standardized Boat Electrofishing: Effect of Catchability on Density and Size Structure Indices. (4th May 2017) - Tyszko, Stephen M.; Hangsleben, Matt A.; Zweifel, Richard D.; Pritt, Jeremy J.; Conroy, Joseph D.
Abstract: Understanding catchability—the fraction of a stock caught by a defined unit of effort—is crucial to using fisheries assessment data to index abundance. We conducted mark–recapture experiments to estimate catchability and evaluate standard boat electrofishing methods for assessing populations of Largemouth Bass Micropterus salmoides . We then used a resampling analysis to test for differences in bass CPUE (fish/h and fish/km) between two high-density reservoirs and one low-density reservoir and among surveys within each reservoir. We compared scenarios using surveys conducted only during (1) the standard time period (mid-April to mid-May) and (2) the entire assessment period (early April to mid-June). We considered the percentage of significant differences in CPUE between the high-density and low-density reservoirs to represent statistical power (i.e., the ability to detect a difference in CPUE when a difference actually exists) and the percentage of significant differences in CPUE between surveys in the same reservoir to represent the false-positive rate (i.e., the detection of a difference in CPUE when no difference in density exists). Catchability and CPUE were greatest and least variable during recapture events conducted during the standard period. The mean catchability of sub–stock length Largemouth Bass (150–200 mm) and memorable-length bass (≥510 mm) was significantly less than those for other length categories. Statistical power exceeded 80%, and the false-positive rate was generally less than 10% for sampling during the standard period at as few as six electrofishing sites. When including samples from outside the standard period, power was lower and the false-positive rate was as high as 60%. Power and false-positive rate were similar whether effort was measured in time or distance. Our results emphasize that standardized springtime boat electrofishing assessments validly index Largemouth Bass density and size structure. Received October 7, 2016; accepted February 2, 2017 Published online April 24, 2017